Sucrose Permeability: A Simple Non-Invasive Marker of Gastro-Duodenal Damage in Dyspepsia - Saha, Tapan Kumar Saha Kumar; Bhattarai, Arabinda Mohan; Sharma, Manushree (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Diagnosis of gastro-duodenal mucosal damage usually requires endoscopy, an invasive procedure. An attempt has been made to assess the clinical validity of sucrose permeability test as a non-invasive marker of gastro-duodenal damage.Methods: The test was carried out in 65 patients of dyspepsia evaluated by endoscopy and 21 healthy controls. On endoscopy, gastro-duodenal epithelial damage was assessed in all patients of dyspepsia and grouped as: group 1 (normal gastro-duodenal mucosa, n=18), group 2 (Gastric ulcer, n=15), group 3 (Duodenal ulcer, n=10), group 4 (Gastritis, n=12) and group 5 (Duodenitis, n=10).Results: The mean urinary sucrose excretions (mg) in 5 hours after 100g oral load was found to be significantly higher in patients of gastric ulcers (183.6 ±169.7, p value < 0.001), duodenal ulcers (151.7± 79.2, p value